Study of bridge damages on local roads in Latvia - Auzins, Roberts; Paeglitis, Ainars (International Conference “Environmental Engineering”, 2020)
Local roads (V class roads) and the bridges on them compose a significant part of the public road network in Latvia. On local roads are around 45% of all bridges located on the national road network. These are mostly reinforced concrete bridges with short or middle span lengths, with one or two traffic lines. Due to low traffic flow, these structures are used lover maintenance classes. The lover maintenance class also includes less de-icing salt in winter maintenance and less founds for maintenance works. At the same time, some of these bridges are located on routes used by heavy timber trucks or trucks taking sand from quarries. Also, agricultural machinery and local people cars are using these bridges for everyday needs. Therefore, the safe exploitation of these structures is essential. Due to different service conditions, the development of deteriorations also will be different. This paper aims to study the development of characteristic types of damages, its causes and consequences and impact on structural performance and service life.